Effects of Acoustic Treatment on Music Teachers’ Exposure to Sound - KOZŁOWSKI, Emil; MŁYŃSKI, Rafał (Archives of Acoustics, 2014)
In this study, music teachers’ exposure to sound was tested by measuring the $A$-weighted equivalent sound pressure level (SPL), the $A$-weighted maximum SPL and the $C$-weighted peak SPL. Measurements were taken prior to and after acoustic treatment in four rooms during classes of trumpet, saxophone, French horn, trombone and percussion instruments. Results showed that acoustic treatment affects the exposure of music teachers to sound. Daily noise exposure levels ($L_{EX, 8\rm\,h}$) for all teachers exceeded a limit of 85$\;$dB while teaching music lessons prior to room treatment. It was found that the $L_{EX,\,8\rm\,h}$ values ranged from 85.8 to 91.6$\;$dB. The highest $A$-weighted maximum SPL and $C$-weighted peak SPL that music teachers were exposed to were observed with percussion instruments ($L_{A\max}$ = 110.4$\;$dB and $L_{C\rm peak}$ = 138.0$\;$dB). After the treatments, daily noise exposure level decreased by an average of 5.8, 3.2, 3.0, 4.2 and 4.5$\;$dB, respectively, for the classes of trumpet, saxophone, French horn, trombone and drums, and did not exceed 85$\;$dB in any case.